Determination of Superior Commodities For The Development of Small and Medium Industries in Kampar Regency - Dewi Diniaty; Anas Miftah Fauzi; Titi Candra Sunarti; Sapta Raharja; Fiora Helmi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The small and medium industries based on superior commodities potentially developed in Kampar Regency, as of its second-largest share contribution of GDP after the agriculture sector. The problem faced in developing small and medium industries is the diverse and varied nature of these enterprises, both in terms of quantity and scope, which leads to unfocused management of potential commodities and types of businesses. A technopark is one of the alternative strategies to develop small and medium industries based on superior commodities. Determining superior commodities is an initial step in developing small and medium industries through technoparks. The purpose of this study is to identify the superior commodities that will be developed in small and medium industries through technoparks in Kampar Regency, Riau Province. Data collection techniques were conducted through literature studies and expert interviews, using purposive sampling. The determination of commodities was done through LQ and SSA. The data used were horticultural crop production from 2017-2021. The study results indicate that pineapples are a superior commodity due to their extensive distribution in five sub-districts, boasting the largest harvest areas, abundant raw materials, and regional potential with LQ >1 and SSA > 0. The development of small and medium industries based on pineapple as a superior commodity through technopark can create economic value in the Kampar Regency.